CALIBRATION OF PLIENSBACHIAN CALCAREOUS NANNOFOSSIL EVENTS IN TWO AMMONITE-CONTROLLED SECTIONS FROM NORTHERN SPAIN(BASQUE-CANTABRIAN AREA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
Common and diverse calcareous nannofossil assemblages were found in two continuous and expanded successions, sedimented on hemipelagic carbonate ramp. Based on refined ammonite biostratigraphy, closely spaced sampling and semiquantitative analysis, the main purpose of this paper is to calibrate against ammonite zones and subzones, the nannofossil composition changes and the identified biohorizons.In the study area, the first notable composition change is in the lower Carixian, with the appearance and abundance increase of the genus Similiscutum, that represents a large amount of the assemblages up to the lower Domerian. Although, the appearance of the genera Biscutum and Bussonius is easily detectable around the Carixian/Domerian boundary, the other relevant Pliensbachian composition changes took place in the lower Domerian. It includes the sharp increase in abundance of the genus Calcivascularis and the appearance of the genus Lotharingius, that dominate the upper Domerian assemblages, also characterized by the significant presence of the genus Biscutum.The set of easily recognizable and reliable events includes the First Occurrences (FOs) of Similiscutum avitum and Similiscutum cruciulus (Jamesoni Zone), the FOs of Lotharingius barozii and Lotharingius hauffii (Stokesi/Margaritatus Zone boundary), the First Common Occurrence (FCO) of Lotharingius hauffii (Margaritatus/Spinatum Zone boundary) and, probably, the FCO of Calcivascularis jansae (Stokesi/Margaritatus Zone boundary). Instead, the FOs of Biscutum dubium, Bussonius prinsii (Davoei Zone), Biscutum novum, Biscutum grande and Biscutum finchii (Stokesi Zone) are slightly difficult to calibrate against ammonite zones.